Association of HIV and highly active antiretroviral therapy with clinical and biochemical indices among women with pre‐eclampsia. Issue 3 (September 2016) - Maharaj, Niren R.; Moodley, Jagidesa; Chuturgoon, Anil
Abstract: Objective: To determine whether clinical and biochemical features associated with pre‐eclampsia are significantly altered among women with HIV infection taking highly active antiretroviral therapy (HAART). Methods: A prospective observational cohort study was conducted between July 2013 and September 2014 at Prince Mshiyeni Memorial Hospital, Durban, South Africa. Women with and without pre‐eclampsia and HIV infection were enrolled at booking and followed up until delivery. Specific demographic data, clinical features, laboratory indices, and complications were analyzed. Results: Of 193 participants, 98 had pre‐eclampsia (45 [45.9%] with HIV infection). There were no significant differences in clinical features and laboratory indices among the study groups except for γ‐glutamyl transferase levels, which were significantly higher among women with pre‐eclampsia and HIV infection (26.9 ± 40.9 U/L) than among those with pre‐eclampsia but no HIV infection (17.1 ± 14.0 U/L; P = 0.001). Perinatal and maternal complications were similar, and there were no maternal deaths. Conclusion: Clinical features, laboratory indices, and complications among women with pre‐eclampsia and HIV infection taking HAART were similar to those among women with pre‐eclampsia without HIV infection. Current guidelines remain appropriate; however, frequent hepatic function tests should be conducted.